2016
DOI: 10.1186/s12953-017-0114-4
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profiling of HBV infected liver biopsies with different fibrotic stages

Abstract: BackgroundHepatitis B virus (HBV) is a global health problem, and infected patients if left untreated may develop cirrhosis and eventually hepatocellular carcinoma. This study aims to enlighten pathways associated with HBV related liver fibrosis for delineation of potential new therapeutic targets and biomarkers.MethodsTissue samples from 47 HBV infected patients with different fibrotic stages (F1 to F6) were enrolled for 2D-DIGE proteomic screening. Differentially expressed proteins were identified by mass sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 48 publications
2
10
0
Order By: Relevance
“…For instance, the randomness of HBV DNA integration events in the host genome adds to the heterogeneity of HBV-related HCC[ 108 ]. Cirrhosis and HCC typically occur more than 20 years after the initial infection[ 109 ]. Smoking, alcohol consumption, aflatoxin exposure, obesity, diabetes, and treatment interventions during this period are strong confounders that also lead to clinical heterogeneity[ 110 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the randomness of HBV DNA integration events in the host genome adds to the heterogeneity of HBV-related HCC[ 108 ]. Cirrhosis and HCC typically occur more than 20 years after the initial infection[ 109 ]. Smoking, alcohol consumption, aflatoxin exposure, obesity, diabetes, and treatment interventions during this period are strong confounders that also lead to clinical heterogeneity[ 110 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study also demonstrated the negative association between PBLD and HCC. Although a number of studies have indicated that PBLD may be involved in HCC progression, the mechanism is unknown (10,20). Additionally, to the best of our knowledge, no effective PBLD activator has been identified.…”
Section: Discussionmentioning
confidence: 99%
“…Unsurprisingly, changes in metabolic process in proteome level were observed. For glucose metabolism, enzymes for glycolysis (hexokinase‐1, hexokinase‐2,6‐phosphofructokinase, aldolase A, phosphoglycerate mutase, and PKM) in the cytoplasm were up‐regulated, and PKM as a potential new therapeutic target and biomarker were found in proteomic profiling of HBV‐infected liver biopsy tissues with different fibrotic stages . Liver injury accelerated glycogenolysis .…”
Section: Discussionmentioning
confidence: 99%